Grammatical Metaphors of Transitivity in Trump’s 2025 Inaugural Speech: A Hallidayian Interpretation - Nguyen Hong, Oanh (BRU ELT JOURNAL, 2025)
Grammatical metaphor, a key concept in Systemic Functional Linguistics, transforms congruent grammatical realisations into metaphorical forms, encoding ideological meaning in political discourse. Despite extensive research on political language, few studies have systematically analysed grammatical metaphors of transitivity in contemporary presidential rhetoric. This study examines grammatical metaphors of transitivity in Donald Trump’s 2025 inaugural address through Hallidayan Systemic Functional Linguistics. Employing clause-by-clause transitivity analysis, the research identifies and categorises instances of metaphorical process realisation, nominalisation patterns, and agency manipulation. The analysis reveals 247 process metaphors, 284 nominalisations, and 239 instances of agency transformation. These linguistic features serve three primary rhetorical functions: presupposing controversial claims as facts, obscuring responsibility for negative outcomes, and constructing an authoritative presidential ethos. The findings demonstrate how grammatical choices encode ideological positioning and shape public interpretation of policy and events. Pedagogical implications for English language teaching are discussed.